Factors related to preparedness for emergency hemodialysis in the event of a natural disaster - Reiko Nihonyanagi, MSN; Keiko Tsukasaki, DSN; Tomoya Itatani, PhD; Hisao Nakai, PhD; Daisuke Toda, PhD (Medicine, 2022)
Abstract. This study aimed to explore patients’ preparedness for emergency hemodialysis in the event of a natural disaster and to determine the factors affecting such preparedness. A cross-sectional study was conducted in undergoing hemodialysis at dialysis facilities in Sapporo, Hokkaido. The participants were a cohort of 256 outpatients aged 20 years or older, 186 (72.7%) were male, and the average age was 61.9 ± 10.9 years. The participants were divided into those who had prepared for emergency dialysis treatment and those who had not. Cross tabulations were performed on the 2 groups using the following participant attributes: preparedness for dialysis during a disaster, knowledge of how to protect themselves during a disaster, and intention to dialyze and evacuate during a disaster, followed by binomial logistic regression analysis. Of the 256 study patients, 184 (71.9%) were not prepared for dialysis treatment. In logistic regression models, patients who were not prepared for dialysis treatment were found to have higher odds of being employed (odds ratio (OR): 2.469; 95% confidence interval (CI): 1.205-5.058), not being aware of disaster information acquisition methods in the event of a disaster (OR: 4.580, 95%; CI: 2.048-10.241), did not receive explanations on proper disaster response from dialysis facility staff (OR: 2.557, 95%; CI: 1.319-4.954), and believing that their family away from home would not be concerned about them (OR: 2.021; 95% CI: 1.062-3.847). Disaster preparedness in patients undergoing dialysis remain inadequate. Dialysis facilities need to strengthen their explanations of disaster response, particularly with regard to working, middle-aged people.